The Relationship of Cognitive Performance and the Theta-Alpha Power Ratio Is Age-Dependent: An EEG Study of Short Term Memory and Reasoning during Task and Resting-State in Healthy Young and Old Adults - Trammell, Janet P.; MacRae, Priscilla G.; Davis, Greta; Bergstedt, Dylan; Anderson, Ariana E. (Frontiers in Aging Neuroscience, 2017)
Objective: The Theta-Alpha ratio (TAR) is known to differ based upon age and cognitive ability, with pathological electroencephalography (EEG) patterns routinely found within neurodegenerative disorders of older adults. We hypothesized that cognitive ability would predict EEG metrics differently within healthy young and old adults, and that healthy old adults not showing age-expected EEG activity may be more likely to demonstrate cognitive deficits relative to old adults showing these expected changes. Methods: In 216 EEG blocks collected in 16 young and 20 old adults during rest (eyes open, eyes closed) and cognitive tasks (short-term memory [STM]; matrix reasoning [RM; Raven’s matrices]), models assessed the contributing roles of cognitive ability, age, and task in predicting the TAR. A general linear mixed-effects regression model was used to model this relationship, including interaction effects to test whether increased cognitive ability predicted TAR differently for young and old adults at rest and during cognitive tasks. Results: The relationship between cognitive ability and the TAR across all blocks showed age-dependency, and cognitive performance at the CZ midline location predicted the TAR measure when accounting for the effect of age (p<0.05, chi-square test of nested models). Age significantly interacted with STM performance in predicting the TAR (p<0.05); increases in STM were associated with increased TAR in young adults, but not in old adults. RM showed similar interaction effects with aging and TAR (p<0.10). Within RM, old adults who had younger-appearing Alpha brain activity were more likely to demonstrate cognitive deficits than old adults who had more typical aging-related Alpha changes (p>0.05). When examining descriptive correlations across the entire sample, which did not surpass multiple comparison corrections, both at rest and during cognitive performance, individual Peak Alpha Frequency (iPAF), relative Delta power, and relative Theta power were generally positively correlated and relative Alpha power was generally negatively correlated with cognitive performance. Conclusion: EEG correlates of cognitive ability are age-dependent. Adults who did not show age-related EEG changes were more likely to exhibit cognitive deficits than those who showed age-related changes. This suggests that healthy aging should produce moderate changes in Alpha and TAR measures, and the absence of